Analisis Forensik Digital Pada Komentar Youtube Live Menggunakan Sentiment Analysis - Uning Kristiana; Alfirna Rizqi Lahitani; Chanief Budi Setiawan; Nafisa Alfi Sa'diya (Jurnal Teknomatika, 2022)
The development of increasingly sophisticated technology can have a positive influence on various aspects of our daily lives. From the survey results of the Indonesian Internet Services Association (APJII) in the second quarter of 2019-2020, it shows that Internet users of the operator spend more time watching online videos. Youtube video content watching is open to the public and all ages can freely watch it. However, the content and comments are not necessarily suitable for audiences of all ages to read. Of course, Youtube video content can also affect behavior, especially minors.The purpose of this research is to conduct digital forensic analysis on Youtube Live Comments using sentiment analysis.The research method used applies the NIST SP 800-86 method, namely Collection, Examination, Analysis, and Reporting. Sentiment analysis resulted in 0.01 in the comments on the two videos tested, namely the PUBG and Free Fire video games. Sentiment analysis resulted in 0.01 in the comments on the two videos tested, namely the PUBG and Free Fire video games.